Utilization of Digital Media to Develop Students' Higher Order Thinking Skills (HOTS) at SD Negeri 3 Anyar, North Lombok - Hikmawati, Hikmawati; Sarbiniwati, Sarbiniwati; Taufiqurrahman, Irwan (Pascasarjana Universitas Mataram, 2024)
HOTS is one of the skills that 21st century students must have. However, not all students have HOTS such as analysis, evaluation and creation. This community service activity aims to develop Students' Higher Order Thinking Skills (HOTS) at SD Negeri 3 Anyar, North Lombok Regency through the use of digital media. The digital media in question are power points and learning videos. This community service activity was carried out at SD Negeri 3 Anyar with the number of participants being all 37 class III students. The activity was carried out on October 14 2023. The activity method was divided into three stages, namely introduction, core and conclusion. The data collection technique for HOTS is carried out by giving an essay test with four questions to activity participants. The percentage of classical completeness is declared complete if 85% of students get a score of more than or equal to 75. The results of the activity show that the average HOTS score for students is 83.4, with a percentage of classical completeness of 92%. Thus, digital media can be used as an alternative learning media to develop HOTS for class III students at SD Negeri 3 Anyar.